KEBERLANJUTAN KEHIDUPAN MASYARAKAT DESA DAN KAITANNYA DENGAN PERUSAHAAN PERKEBUNAN (Kajian Pemanfaatan Lahan dan Kehidupan Masyarakat Sekitar Perusahaan Perkebunan Kelapa Sawit di Provinsi Jambi) - Rosjani Rosjani (EKOTON, 2013)
The growing of oil palm plantations in the areas inhabited by the Suku Anak Dalam communities in Jambi province, has led peoples to be squeezed. The places where the SAD communities fulfill their social functions has become a sea of plantations and oil palm industry. SAD and villager communities are found on the land awarded to the plantation companies. The relationships between the three threaten the SAD both socially and culturally systems. The model also taken into consideration interaction seen from social, physical, economic and institutional aspek for villagers. This model also given benefit to oil palm plantation in ecologis, economic and protecting companies.